Symptomatic IgG4-Related Prostatitis Simultaneously Diagnosed with Aggressive Prostate Cancer. (4th March 2020) - Ezaki, Taisuke; Akatsuka, Seiya; Sanjo, Tansei; Masuda, Takeshi
Abstract : IgG4-related disease is a systemic fibroinflammatory disorder that occasionally affects the prostate. It is usually considered that patients with IgG4-related disease are at high risk of developing malignancies. A 71-year-old man presented to our hospital with a chief complaint of urinary retention. Prostate biopsy revealed concomitant IgG4-related prostatitis and prostate cancer. IgG4-related prostatitis was a possible cause of urinary retention, and the aggressive nature of prostate cancer was the cause of the patient's death 2 years after diagnosis. This is the fourth case report of prostate cancer accompanied by IgG4-related prostatitis; however, there have been no reports of the two diseases coexisting with high clinical significance. Our case report indicates that patients diagnosed with IgG4-related prostatitis should be carefully followed up considering the risk of prostate cancer.